Hubungan Motivasi Dan Pengetahuan Dengan Kepatuhan Pelaksanaan Diet Pada Penderita Diabetes Melitus Di Poliklinik Di RSUD Leuwiliang Tahun 2021: Relationship Between Motivation and Knowledge with Adherence to Diet in Patients with Diabetes Mellitus at the Leuwiliang Hospital Polyclinic in 2021 - Widyanti, Lidiya (Dohara POAJ, 2022)
Introduction: Adherence to the implementation of the diabetes mellitus diet is the level of patients carrying out the treatment and behavior suggested by their doctor or by other medical teams to make arrangements for eating methods that have the aim to reduce complications of the disease, for example in the diabetes mellitus diet. This study aims to find out the relationship between motivation and knowledge with the compliance of dietary implementation in people with diabetes mellitus in Polyclinics at Leuwiliang Hospital in 2021. Methods: The research used is the descriptive correlation with cross-sectional approaches. The population in this study amounted to 130 people with diabetes mellitus. The samples were taken with a simple random sampling technique in 125 people with diabetes mellitus. The instrument used is a questionnaire. Results: Analysis of data using univariate and bivariate data using the Chi-Square test. The results of this study showed that there is a motivational relationship (p-value = 0,000) with adherence to dietary implementation in people with diabetes mellitus. There is a relationship between knowledge (p-value = 0,002)) and adherence to dietary implementation in people with Diabetes Mellitus. Discussion: There is a relationship between motivation and knowledge with adherence to dietary implementation in people with diabetes mellitus in Polyclinics at Leuwiliang Hospital in 2021. Of the 125 people with diabetes mellitus whose motivation is less (48,0%) do not adhere to the implementation of the diet and less knowledge (36,8%) do not comply with the implementation of the diet.